(untitled) (Revista Contexto & Educação, 2025)
This research sought to understand how the School Paralympics had an impact on the historical constitution of school paralympic sport in Rio Grande do Sul (RS), from 2010 to 2019, based on oral testimonies from Physical Education teachers and coaches(as) sports. Information collection was carried out through semi-structured interviews with 11 participants and the material was subjected to the Thematic Content Analysis technique. The results highlighted the challenges and practices carried out by two Physical Education teachers to enable the participation of the state’s first delegation in the School Paralympics, in 2010. Along the same path, other agents and institutions began to share interests and develop practices focused on school paralympic sports in the state, forming the “State Parasports Center”. Actions such as events, competitions, projects and training focused on sport for students with disabilities began to be carried out in different municipalities in the state. The reports of the interviewees point to representations that show pride in the practices consolidated around school paralympic sports based on the interrelationships of the aforementioned nucleus. On the other hand, signs of discontent were found regarding the lack of State policies that ensure sport for students with disabilities in the long term.